THE ROLE OF A LAWYER IN THE LIFE OF SOCIETY AND THE STATE (SCIENTIFIC AND PRACTICAL ROUND TABLE) - Шумський, Петро Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
Scientific-practical round table.